Pengembangan Multimedia Pembelajaran Berbasis Komputer - Dwi Priyanto (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
in 21st century globalization and information era, information become one critical resource that determining global competence. Meanwhile, education role become determining factor that encourage technology transfer, adaptation and its propagation. One of technology effect in education and learning are availability learning resources and media for learner. Therefore, teacher, instructor, or lecturer not becomes only one information source. Because learning process identical with information transmission process or communication process, therefore learning media have to be more innovative and interactive, example learning multimedia designed with computer aided known as CBI or Computer-Based Instructional.Â